Role of sulphate on corrosion inhibition of aluminium alloy in acidic environment / Norshamira Mazlan - Norshamira , Mazlan (2022)
Acid accelerates the corrosion process of aluminium. In this study, sulphate is used to study the corrosion inhibition on 5052 aluminium alloy surfaces. Sodium sulphate is added into different pH of acid solution. Concentrated sodium hydroxide was used to alter the pH of concentrated hydrochloric acid to get the desired pH 2, pH 4 and pH 6. Distilled water is used to prepare pH 7 to compare the behaviour of sulphate in acid and neutral electrolytes. Potentiodynamic polarisation measurement was employed to evaluate the electrochemical characteristics of the aluminium samples. While assessing the performance of the inhibitors, the effect of inhibitor concentrations in the acidic and neutral electrolytes are also to be studied. The corrosion rates of the aluminium samples were reduced when sulphate inhibitor was added into the acidic electrolyte. It is found that the corrosion density of aluminium samples was reduced with increasing inhibitor concentration until 400 mg/L in all pH conditions and the maximum efficiency is identified at pH 6 with 67.4% . From Tafel plots, sulphate acts as anodic-dominant inhibitor in acidic environment. The corroded samples were analysed under optical microscope for surface characterisation. The morphological images study on aluminium alloy samples perceived that uniform corrosion happened on the aluminium surface with slightly pitting on certain areas.